Inter- and Intra-Observer Variation of the Schatzker and AO/OTA Classifications of Tibial Plateau Fractures and a Proposal of a New Classification System - Charalambous, CP (The Royal College of Surgeons of England, 2007)
INTRODUCTION: The aim of this study was to evaluate the intra- and inter-observer variation of the Schatzker and AO/OTA classifications in assessing tibial plateau fractures, using plain radiographs. PATIENTS AND METHODS: Fifty tibial plateau fractures were classified independently by six observers as per the Schatzker and AO/OTA classifications, using antero-posterior and lateral plain radiographs. Assessment was done on two occasions, 8 weeks apart. RESULTS: We found that both the Schatzker and AO/OTA classifications have a high intra-observer (κ = 0.57 and 0.53, respectively), and inter-observer (κ = 0.41 and 0.43, respectively) variation. Classification of tibial plateau fractures into unicondylar versus bicondylar and pure splits versus articular depression ± split conferred improved inter- and intra-observer variation. CONCLUSIONS: The high inter-observer variation found for the Schatzker and AO/OTA classifications must be taken into consideration when these are used as a guidance of treatment and when used in evaluating patients' outcome. Simply classifying tibial plateau fractures into unicondylar versus bicondylar and pure splits versus articular depression ± split may be more reliable.